LEGAL DISCOURSE: TEXT ANALYSIS AND TRANSLATION STRATEGIES - VELYKODSKA, Olena (Comparative Legilinguistics, 2019)
The article deals with basic requirements to the translation for specific purposes, namely legal translation. The problem posed here is defining object and theoretical basis of legal translation. The question of the necessity of information search as an integral part of translation strategy has been raised. Detailed analysis revealed that the requirements of professional translators include knowledge of lexical and grammatical peculiarities of both languages in legal sphere; deep understanding of the concepts employed by specialists in particular field and the specialist terms used to express these concepts and their relationships in the source and target languages. It is recommended that evaluation of the translation may be done on the following principles: communicative pragmatic norms of translation; equivalent norms of translation; absence of contextual, cultural, functional, lexico-grammatical mistakes.